Investigation of some structural and optical properties of lithium sodium fluoroborate glasses containing cuprous oxide. (February 2018) - Hammad, Ahmed H.; Elsaghier, H.M.; Abbas, W.; Zidan, Nehad A.; Marzouk, Samir Y.
Graphical abstract: Highlights: Lithium sodium borate glasses were modified by fluorine and cuprous ions. Non-bridging oxygens were formed as copper ions increases. Fluorine ions modify the structural borate units to BO2 F/BO3 F units. Empirical formula between Λ(no ) and no is experimentally predicted. Abstract: Lithium sodium fluoroborate glasses containing Cu2 O were investigated in terms of structural and optical modification. The measured density values are observed to increase as Cu2 O increase related to the replacement of some alkali cations by the higher density copper ions. Infrared absorption spectra for the investigated glasses show the characteristic structural bands or peaks for triangular and tetragonal borate units and the presence of fluorine ions may cause a replacement of some BO3 /BO4 units by BO2 F/BO3 F units, respectively. Optical band gap values are observed to decrease from 3.402 to 1.7 eV as the copper content increase. The refractive index values are varied from 2.296 to 2.880 as the copper content changed. The studied glasses tend to metallicity when copper ions embedded to borate network. Oxide/fluoride ions polarizability and optical basicity are correlated to the linear refractive index. The optical basicity based on refractive index behaves linearity associated with refractive index.